1994
DOI: 10.1902/jop.1994.65.10.908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Conventional Probe With Electronic and Manual Pressure‐Regulated Probes

Abstract: We compared the accuracy, consistency, time, comfort, and cost of probing with a conventional hand probe (CP) with 3-mm banded markings, a manual pressure-regulated probe (MP), and two electronic probes (IP and FP). Twenty (20) examiners used all four probes on a test block to determine accuracy; measurements compared favorably to the reference block. Two calibrated examiners probed the Ramfjord teeth of 10 periodontal patients on maintenance regimens, six sites per tooth (n = 708), with all four probes; measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 12 publications
3
30
2
4
Order By: Relevance
“…One common problem was encountered as the underestimation of deep probing depths by the automated probe, which is similar to the study by Perry D A et al 1994. 18 The comparative evaluation between the conventional Williams periodontal probe and Florida probing system in the present study has confirmed that efficacy of Florida probing system for measurement of probing depth and clinical attachment levels is more consistent. It is recommended for multicentre study employing larger numbers of subjects and examiners for further evaluation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…One common problem was encountered as the underestimation of deep probing depths by the automated probe, which is similar to the study by Perry D A et al 1994. 18 The comparative evaluation between the conventional Williams periodontal probe and Florida probing system in the present study has confirmed that efficacy of Florida probing system for measurement of probing depth and clinical attachment levels is more consistent. It is recommended for multicentre study employing larger numbers of subjects and examiners for further evaluation.…”
Section: Discussionsupporting
confidence: 80%
“…Also, clinicians need to be trained to operate these probes. 8 Aim of this study was to assess and compare the accuracy of the Florida probe and Williams periodontal probe in determining the periodontal pocket depth and clinical attachment level. The objectives of study was to determine whether Florida probe is better in determining periodontal pocket depth when compared with Williams periodontal probe and also to determine whether CEJ probe (a component of Florida probe system) is better in determining CAL when compared with Williams periodontal probe.…”
Section: Introductionmentioning
confidence: 99%
“…Our study went further than previously reported work, 6,[9][10][11][12][13][14][15] in that we calculated these values of reliability at both the quadrant and the tooth level. We observed similar ranges of values regardless of which measure was assessed.…”
Section: Discussionmentioning
confidence: 79%
“…In terms of reproducibility of measurements for probing pocket depths and attachment loss, studies performed by Perry et al (1994) and Tupta-Veselicky et al (1994) suggested that there were no significant advantages in the use of second or third generation probes [56,57]. This was also confirmed in a systematic review of clinical trials evaluating the reproducibility of manual (MP) and electronic probes (EP) in the measurement of clinical periodontal attachment level (AL) in untreated periodontitis subjects [58].…”
Section: Current Situationmentioning
confidence: 99%